Anti-static composite geomembrane and preparation method thereof
By using anti-static composite rubber and anti-corrosion reinforcement fillers in geomembrane, the various properties of geomembrane are improved, and the problems of insufficient performance and short service life of ordinary geomembrane in extreme operating conditions are solved, achieving wider application and longer service life.
Patent Information
- Application Number
- CN202411524885.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Ordinary geomembranes are unable to follow their strength in extreme working conditions, and are not able to be worn and anti-corrosion, making them difficult to repair, resulting in a short service life and lack of anti-static characteristics, which poses safety hazards.
Anti-static composite rubber and corrosion-resistant enhancement filler are used to participate in the preparation of geomembrane. By synthesizing anti-static composite rubber and corrosion-resistant enhancement filler, the anti-static ability, corrosion resistance, impact resistance and high temperature resistance of geomembrane are improved, and micro cracks are repaired through the fracture and recombination capabilities of disulfide bonds.
It significantly improves the anti-static ability, corrosion resistance, impact resistance and high temperature resistance of geomembrane, extends the service life of geomembrane, and expands its application areas, which can meet the needs of use in a variety of environments.
Smart Images

Figure CN119613840A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geomembranes, and in particular to an antistatic composite geomembrane and a preparation method thereof. Background Art
[0002] With the rapid development of modern engineering technology, geomembranes, as indispensable geosynthetics, are becoming more and more important in the construction of anti-leakage systems for water conservancy projects, the enhanced isolation of transportation infrastructure, the safe treatment of landfills in the environmental protection industry, and the promotion of efficient agricultural irrigation, providing solid technical support for the development and progress of these fields. However, in the face of increasingly complex and changing engineering environments and ever-increasing performance requirements, ordinary geomembranes have gradually exposed their limitations. Although the mechanical properties of ordinary geomembranes can meet basic needs, they are unable to do so under extreme working conditions. The lack of wear resistance and corrosion resistance has greatly reduced the isolation and anti-seepage effects after long-term service, especially in places such as electronic precision manufacturing and chemical storage that require extremely high static control. Ordinary geomembranes lack antistatic properties, which not only easily absorb dust and affect the working environment, but are also likely to cause fires or electric shock accidents due to static electricity accumulation, posing a safety hazard. At the same time, under extreme environmental conditions such as high temperature and strong corrosion, the durability of ordinary geomembranes is significantly reduced, cracks are easily generated, and they are difficult to repair. They cannot meet the needs of diversified application scenarios, which seriously limits the use of geomembranes.
[0003] The patent with announcement number CN108384136B announces a graphene geomembrane and its preparation method and application. The raw materials of this graphene geomembrane include petroleum resin and graphene, which has excellent mechanical properties and anti-seepage ability, and does not generate static electricity, so that it can be widely used in garbage, hazardous chemical waste, radioactive waste landfills, as well as oil and gas fields, chemical areas and other oil and gas explosion-proof places. However, the graphene geomembrane prepared by this patent uses graphene as raw material, which has a high cost, limiting its use in projects with high economic requirements. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-static composite geomembrane and a preparation method thereof, which solves the following technical problems: (1) The mechanical properties of ordinary geomembranes need to be improved, and their corrosion resistance and wear resistance are insufficient. Once cracks are generated, they are difficult to repair, resulting in a short service life; (2) Ordinary geomembranes have poor anti-static ability and are not resistant to high temperatures, making it difficult to meet the use requirements in various environments.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic composite geomembrane comprises the following raw materials in parts by weight: 22-25 parts of high-density polyethylene, 16-20 parts of linear low-density polyethylene, 8-12 parts of maleic anhydride grafted high-density polyethylene, 1-3 parts of ultraviolet absorber, 1.5-2.5 parts of antioxidant, 2-3 parts of plasticizer, 3-5 parts of lubricant, 8-10 parts of antistatic composite rubber, and 6-8 parts of anti-corrosion reinforcing filler.
[0006] Furthermore, the ultraviolet absorber is any one of ultraviolet absorber UV-1164, ultraviolet absorber UV-1577, and ultraviolet absorber UV-3030; the antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the plasticizer is any one of diisononyl phthalate, triethyl citrate, and epoxy soybean oil; and the lubricant is any one of polyethylene wax, paraffin, and white oil.
[0007] Furthermore, the preparation method of the antistatic composite rubber comprises the following steps: S1: placing EPDM rubber in toluene, mixing and stirring thoroughly, adding allyl glycidyl ether and initiator, heating to 65-70°C for reaction for 5-6h, removing the solvent by vacuum distillation, and collecting the product to obtain epoxidized EPDM rubber; S2: placing epoxidized ethylene propylene diene rubber and 2,2'-disulfide dipyridine in N,N-dimethylformamide, heating the mixture for reaction, and collecting the product after reduced pressure distillation to obtain an antistatic composite rubber.
[0008] Furthermore, the initiator is any one of benzoyl peroxide and dicumyl peroxide.
[0009] In this scheme, under the action of an initiator, the double bonds in the EPDM rubber structure react with the double bonds in the allyl glycidyl ether structure to undergo free radical polymerization to obtain epoxidized EPDM rubber, and the epoxy groups in the epoxidized EPDM rubber structure react with the tertiary amine in the 2,2'-disulfide dipyridine structure to undergo quaternization to obtain an antistatic composite rubber containing quaternary ammonium groups in the structure. This antistatic composite rubber is involved in the preparation process of geomembrane. The good elasticity of the EPDM rubber selected as its matrix can effectively enhance the flexibility of the geomembrane and improve its impact resistance. The quaternary ammonium group in its structure can make the geomembrane have excellent antistatic ability, effectively prevent safety hazards such as electric shock, sparks and even explosions caused by static electricity accumulation, so that it can be used in electronic factories, oil and gas projects, chemical plants and other static-sensitive environments, effectively expanding the use of geomembranes. At the same time, its structure also has multiple hydroxyl groups, which can interact with the geomembrane matrix material, effectively enhancing the compatibility between the antistatic composite rubber and the matrix material, making the two more closely combined. The disulfide bonds in its structure have the ability to break and recombine. When the geomembrane is actually used, the tiny cracks in the geomembrane are effectively repaired, thereby preventing the cracks from expanding, effectively avoiding the probability of larger cracks, and greatly extending the service life of the geomembrane.
[0010] Furthermore, in step S2, the temperature of the temperature-raising reaction is 70-80° C. and the time is 6-8 hours.
[0011] Furthermore, the preparation method of the anti-corrosion reinforcing filler comprises the following steps: SS1: Place rectorite in deionized water, introduce nitrogen, and ultrasonically disperse for 10-15 minutes, then add chloroethyl isocyanate and a catalyst, heat to 75-80°C, react for 3-5 hours, filter, wash, and dry to obtain chloroethyl rectorite; SS2: Place chloroethyl rectorite in chloroform, ultrasonically disperse for 15-20 minutes, introduce nitrogen, add polyetheretherketone and anhydrous tin tetrachloride, heat and reflux for 8-10 hours, filter, wash and dry to obtain the corrosion-resistant reinforcing filler.
[0012] In this scheme, under the action of a catalyst, the isocyanate group in the structure of chloroethyl isocyanate interacts with the hydroxyl group on the surface of the rectorite to obtain chloroethyl rectorite, and then under the catalytic action of anhydrous tin tetrachloride, polyetheretherketone reacts with the active chlorine in the structure of chloroethyl rectorite to obtain an anti-corrosion reinforcing filler. This anti-corrosion reinforcing filler has good dispersibility in the geomembrane matrix material, can effectively enhance the wear resistance and tensile strength of the geomembrane, connects the polyetheretherketone with the rectorite in a chemically bonded manner, combines the barrier ability of the lamellar rectorite with the anti-corrosion ability of the polyetheretherketone, can effectively enhance the anti-corrosion ability of the geomembrane, and can stably play a barrier role even in the presence of corrosive media. At the same time, the polyetheretherketone coated on its surface also has excellent wear resistance and high temperature resistance, which can further enhance the wear resistance of the geomembrane, enhance the high temperature resistance of the geomembrane, expand its application field, and extend its service life.
[0013] Furthermore, in step SS1, the catalyst is any one of dibutyltin dilaurate and stannous octoate.
[0014] Furthermore, in step SS2, the molecular weight of the polyetheretherketone is 30,000-50,000.
[0015] A method for preparing an antistatic composite geomembrane comprises the following steps: Step 1: Place high-density polyethylene, linear low-density polyethylene, maleic anhydride grafted high-density polyethylene, ultraviolet absorber, antioxidant, plasticizer, lubricant, antistatic composite rubber, and anti-corrosion reinforcing filler in a mixer, heat to 185-195° C., mix for 1-1.5 hours, and obtain a mixture; Step 2: Place the mixed material in a single screw extruder, blow it into a film after melting and extruding, and cut and roll it up after cooling to obtain a geomembrane.
[0016] Furthermore, in step 2, the front section temperature of the single screw extruder is 200-210°C, the rear section temperature is 210-220°C, and the head temperature is 220-230°C.
[0017] Beneficial effects of the present invention: The present invention prepares antistatic composite rubber and anti-corrosion reinforcing fillers in the preparation process of geomembrane, so that the prepared geomembrane has excellent antistatic ability, anti-corrosion ability, impact resistance, high mechanical strength, good wear resistance, high temperature resistance and the ability to repair tiny cracks, can meet the use requirements in various environments, and has a long service life.
[0018] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 It is the thermal weight loss curve of the rectorite, chloroethyl rectorite and the anti-corrosion filler of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The preparation method of the antistatic composite rubber and the anti-corrosion reinforcing filler described in the following examples and comparative examples of the present invention is as follows: 1. Preparation of antistatic composite rubber S1: 4 g of EPDM rubber was placed in 80 ml of toluene, and the mixture was stirred thoroughly. 3.5 g of allyl glycidyl ether and 0.8 g of benzoyl peroxide were added, and the mixture was heated to 65° C. for reaction for 5 h. After the solvent was removed by vacuum distillation, the product was collected to obtain epoxidized EPDM rubber. S2: 4.2 g of epoxidized ethylene propylene rubber and 3.6 g of 2,2'-disulfide dipyridine were placed in 100 ml of N,N-dimethylformamide, the temperature was raised to 70° C. for reaction for 6 h, and the product was collected after reduced pressure distillation to obtain an antistatic composite rubber.
[0023] The content of quaternary ammonium groups in the antistatic composite rubber was determined by the silver titration method. 1g of the antistatic composite rubber was weighed as a sample, placed in a 100ml volumetric flask, diluted to the scale with solvent, shaken, 10ml was transferred to a 150ml conical flask, 1ml of potassium chromate indicator was added, and titrated with a silver nitrate standard solution with a concentration of 0.05ml / L until the precipitate in the solution no longer changed. The content of quaternary ammonium groups in the sample was calculated by the following formula: Content of quaternary ammonium groups in the sample (%) = CVM×100% / 0.1m; Wherein: C is the concentration of the silver nitrate standard solution, mol / L; V is the volume of silver nitrate consumed in the titration, ml; m is the mass of the sample, g; M is the molar mass of the sample, g / mol. After calculation, the content of quaternary ammonium groups in the sample is 8.45%, indicating that quaternary ammonium groups exist in the final antistatic composite rubber.
[0024] 2. Preparation of anti-corrosion reinforced filler SS1: 3 g of rectorite was placed in 100 ml of deionized water, nitrogen was introduced, and ultrasonic dispersion was performed for 10 min. Then, 2.8 g of chloroethyl isocyanate and 0.3 g of dibutyltin dilaurate were added. The temperature was raised to 75 °C and reacted for 3 h. After filtration, washing and drying, chloroethyl rectorite was obtained. SS2: Place 3.2 g of chloroethyl rectorite in 150 ml of chloroform, ultrasonically disperse for 15 minutes, introduce nitrogen, add 3.5 g of polyetheretherketone with a molecular weight of 30,000 and 0.5 g of anhydrous tin tetrachloride, heat and reflux for 8 hours, and filter, wash and dry to obtain an anti-corrosion reinforcing filler.
[0025] Thermogravimetric analysis was performed on rectorite, chloroethyl rectorite and anti-corrosion filler. Figure 1 It can be seen that the final mass retention rate of rectorite at high temperature is 96.5%, and the lost part is caused by the thermal decomposition of crystal water; the final mass retention rate of chloroethyl rectorite is 49.9%, and the lost part is caused by the thermal decomposition of chloroethyl isocyanate on its surface; the final mass retention rate of anti-corrosion reinforcing filler is 23.8%, and the lost part is caused by the thermal decomposition of organic matter on its surface. Example
[0026] Preparation method of geomembrane Step 1, 22 parts of high-density polyethylene, 16 parts of linear low-density polyethylene, 8 parts of maleic anhydride grafted high-density polyethylene, 1 part of ultraviolet absorber UV-1164, 1.5 parts of antioxidant 1010, 2 parts of diisononyl phthalate, 3 parts of polyethylene wax, 8 parts of antistatic composite rubber, and 6 parts of anti-corrosion reinforcing fillers are placed in a mixer, heated to 185° C. and mixed for 1 hour to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 200°C, the rear section temperature to 210°C, and the head temperature to 220°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane. Example
[0027] Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, 4 parts of paraffin wax, 9 parts of antistatic composite rubber, and 7 parts of anti-corrosion reinforcing filler are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane. Example
[0028] Preparation method of geomembrane Step 1, 25 parts of high-density polyethylene, 20 parts of linear low-density polyethylene, 12 parts of maleic anhydride grafted high-density polyethylene, 3 parts of ultraviolet absorber UV-3030, 2.5 parts of antioxidant 168, 3 parts of epoxy soybean oil, 5 parts of white oil, 10 parts of antistatic composite rubber, and 8 parts of anti-corrosion reinforcing filler are placed in a mixer, heated to 195° C. and mixed for 1.5 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 210°C, the rear section temperature to 220°C, and the head temperature to 230°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0029] Comparative Example 1 Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, 4 parts of paraffin wax, and 9 parts of antistatic composite rubber are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0030] Comparative Example 2 Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, 4 parts of paraffin wax, and 7 parts of anti-corrosion reinforcing filler are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0031] Comparative Example 3 Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, and 4 parts of paraffin are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0032] Comparative Example 4 Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, 4 parts of paraffin wax, 9 parts of ethylene propylene diene rubber, and 7 parts of anti-corrosion reinforcing filler are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0033] Comparative Example 5 Preparation method of geomembrane Step 1, 23 parts of high-density polyethylene, 18 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted high-density polyethylene, 2 parts of ultraviolet absorber UV-1577, 2 parts of antioxidant 1076, 2.5 parts of triethyl citrate, 4 parts of paraffin wax, 9 parts of antistatic composite rubber, and 7 parts of rectorite are placed in a mixer, heated to 190° C. and mixed for 1.2 hours to obtain a mixture; Step 2: Place the mixture in a single-screw extruder, set the front section temperature of the extruder to 205°C, the rear section temperature to 215°C, and the head temperature to 225°C, blow mold into a film after melt extrusion, trim and roll up after cooling to obtain a geomembrane.
[0034] Performance Testing ① The geomembranes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were made into samples that met the specifications using a universal sample making machine. The impact strength of the samples was tested with reference to standard GB / T1043.1-2008 to determine the flexibility and impact resistance of the samples. The Vicat softening temperature of the samples was tested with reference to standard GB / T1633-2000 to determine the high temperature resistance of the samples. The samples were immersed in 1.5 mol / L hydrochloric acid solution and 1.5 mol / L sodium hydroxide solution for 1 0.5 mol / L of water for 1 0.5 mol / L of water. 0h, record the weight loss of the sample, judge the corrosion resistance of the sample, and calculate the weight loss rate by the following formula: Weight loss rate (%) = (m-m1) / m; where m is the mass of the sample, g; m1 is the mass of the sample after immersion treatment, g; place the sample on the sample table of the GSL-46 steel wool friction tester, place a 1000g load weight, rub the sample back and forth at a rate of 15mm / s, repeat 100 cycles, observe the scratches on the sample surface after the end, and conduct a wear resistance test; the specific test results are shown in the table below:
[0035] It can be seen from the above table that the geomembranes prepared by Examples 1 to 3 and Comparative Examples 1 to 5 all have excellent impact resistance, high temperature resistance, corrosion resistance and wear resistance. No anti-corrosion reinforcing additives were added to the sample prepared in Comparative Example 1, and the corrosion resistance and wear resistance were average. No anti-static composite rubber was added to the sample prepared in Comparative Example 2, and the impact resistance was not as good as that of the embodiment. Neither anti-static composite rubber nor anti-corrosion reinforcing additives were added to the sample prepared in Comparative Example 3, so the wear resistance, corrosion resistance, high temperature resistance and impact resistance were not as good as those of the embodiment. No anti-static composite rubber was added to the sample prepared in Comparative Example 4, but EPDM rubber was directly added. The impact resistance, high temperature resistance, corrosion resistance and wear resistance of the sample prepared in Comparative Example 5 were not as good as those of the embodiment. This is because no anti-corrosion reinforcing filler was added to the sample, and rectorite was directly added, resulting in agglomeration of rectorite in the sample.
[0036] ② The geomembranes prepared in Example 1-Example 3 and Comparative Example 1-Comparative Example 5 were made into samples that met the specifications using a universal sample making machine, and the surface resistivity of the samples was tested using a DRK321B-II surface resistivity tester to determine the antistatic ability of the samples; a crack 3 cm long and about 0.5 mm wide was scratched on the surface of the sample, and repaired at 150°C for 24 hours. The tensile strength of the repaired sample and the initial tensile strength of the sample were tested with reference to the standard GB / T1040.2-2022, and the sample repair rate was calculated by the following formula: repair rate = (tensile strength after repair / initial tensile strength) × 100%, and the sample repair ability and mechanical properties were determined. The specific test results are shown in the table below:
[0037] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have good mechanical strength, good antistatic effect and self-repair ability. The sample prepared in Comparative Example 1 has strong antistatic ability and good repair ability, which is due to the addition of antistatic composite rubber, while the samples prepared in Comparative Example 2, Comparative Example 3 and Comparative Example 4 have poor antistatic ability and repair ability, which is due to the fact that the prepared geomembrane structure does not contain quaternary ammonium groups and disulfide bonds. In the sample prepared in Comparative Example 5, although antistatic composite rubber is added, the directly added rectorite produces agglomeration in the matrix, which results in the antistatic ability and self-repair ability being inferior to those of the embodiments.
[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0039] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An antistatic composite geomembrane, characterized in that: The invention comprises the following raw materials in parts by weight: 22-25 parts of high-density polyethylene, 16-20 parts of linear low-density polyethylene, 8-12 parts of maleic anhydride grafted high-density polyethylene, 1-3 parts of ultraviolet absorber, 1.5-2.5 parts of antioxidant, 2-3 parts of plasticizer, 3-5 parts of lubricant, 8-10 parts of antistatic composite rubber and 6-8 parts of anti-corrosion reinforcing filler.
2. The antistatic composite geomembrane according to claim 1, characterized in that: The ultraviolet absorber is any one of ultraviolet absorber UV-1164, ultraviolet absorber UV-1577, and ultraviolet absorber UV-3030; the antioxidant is any one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the plasticizer is any one of diisononyl phthalate, triethyl citrate, and epoxy soybean oil; and the lubricant is any one of polyethylene wax, paraffin, and white oil.
3. The antistatic composite geomembrane according to claim 1, characterized in that: The preparation method of the antistatic composite rubber comprises the following steps: S1: placing EPDM rubber in toluene, mixing and stirring thoroughly, adding allyl glycidyl ether and initiator, heating to 65-70°C for reaction for 5-6h, removing the solvent by vacuum distillation, and collecting the product to obtain epoxidized EPDM rubber; S2: placing epoxidized ethylene propylene diene rubber and 2,2'-disulfide dipyridine in N,N-dimethylformamide, heating the mixture for reaction, and collecting the product after reduced pressure distillation to obtain an antistatic composite rubber.
4. The antistatic composite geomembrane according to claim 3, characterized in that: In step S1, the initiator is any one of benzoyl peroxide and dicumyl peroxide.
5. The antistatic composite geomembrane according to claim 3, characterized in that: In step S2, the temperature of the temperature-raising reaction is 70-80° C. and the time is 6-8 hours.
6. The antistatic composite geomembrane according to claim 1, characterized in that: The preparation method of the anti-corrosion reinforcing filler comprises the following steps: SS1: Place rectorite in deionized water, introduce nitrogen, and ultrasonically disperse for 10-15 minutes, then add chloroethyl isocyanate and a catalyst, heat to 75-80°C, react for 3-5 hours, filter, wash, and dry to obtain chloroethyl rectorite; SS2: Place chloroethyl rectorite in chloroform, ultrasonically disperse for 15-20 minutes, introduce nitrogen, add polyetheretherketone and anhydrous tin tetrachloride, heat and reflux for 8-10 hours, filter, wash and dry to obtain the corrosion-resistant reinforcing filler.
7. The antistatic composite geomembrane according to claim 6, characterized in that: In step SS1, the catalyst is any one of dibutyltin dilaurate and stannous octoate.
8. The antistatic composite geomembrane according to claim 6, characterized in that: In step SS2, the molecular weight of the polyetheretherketone is 30000-50000.
9. A method for preparing an antistatic composite geomembrane as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Place high-density polyethylene, linear low-density polyethylene, maleic anhydride grafted high-density polyethylene, ultraviolet absorber, antioxidant, plasticizer, lubricant, antistatic composite rubber, and anti-corrosion reinforcing filler in a mixer, heat to 185-195° C., mix for 1-1.5 hours, and obtain a mixture; Step 2: Place the mixed material in a single screw extruder, blow it into a film after melting and extruding, and cut and roll it up after cooling to obtain a geomembrane.
10. The method for preparing an antistatic composite geomembrane according to claim 9, characterized in that: In step 2, the temperature of the front section of the single screw extruder is 200-210°C, the temperature of the rear section is 210-220°C, and the temperature of the die head is 220-230°C.
Citation Information
Patent Citations
Graphene geomembranes, their preparation methods and applications
CN108384136B
Environmental-friendly polyvinyl chloride (PVC) extraction-resistant anti-seepage film and preparation method thereof
CN103497446A
Composite geomembrane for building
CN204982973U
Antistatic polyether-ether-ketone composite material and preparation method therefor
WO2024066693A1
Cited By
Electrostatic dustproof geomembrane and application thereof
CN122383022A